2012
DOI: 10.5582/ddt.2012.v6.4.205
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and hepatoprotective activity of an ethanol extract of Syzygium jambos (L.) leaves

Abstract: Herbal medicines have traditionally been used worldwide for the prevention and treatment of liver disease with fewer adverse effects. The leaves of the Syzygium jambos (SJL) plant were chosen and studied for their antioxidant activity in vitro and hepatoprotective activity in vivo. The antioxidant activity of the ethanol extract was examined in vitro using a 1,1-diphenyl-2-picrylhydrazyl (DPPH) free radical scavenging assay, reducing capacity, total phenol, total flavonoid content, and total antioxidant capaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 36 publications
1
27
0
Order By: Relevance
“…The antioxidant activity of compounds was evaluated by measuring its scavenging capacity for the DPPH free radical (Islam et al, 2012). Therefore, DPPH assay, superoxide anion radical scavenging assay, and hydroxyl free radical scavenging assay were used as relevant indicator of antioxidant activity.…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidant activity of compounds was evaluated by measuring its scavenging capacity for the DPPH free radical (Islam et al, 2012). Therefore, DPPH assay, superoxide anion radical scavenging assay, and hydroxyl free radical scavenging assay were used as relevant indicator of antioxidant activity.…”
Section: Discussionmentioning
confidence: 99%
“…Syzygium jambos is an evergreen tree of the family Myrtaceae, it was reported that several phenolic compounds and triterpenes have been isolated from the leaves of the S. jambos [8][9][10]. Moreover, S. jambos showed antioxidant, antiviral [11], anti-inflammatory [12], and antimicrobial activity [13].…”
Section: Introductionmentioning
confidence: 99%
“…Proliferation of tissue in vivo can be evaluated by DNA synthesis (Ueda et al, 2005). Acrylamide toxicity in rats showed that hepatic tissue produces large amounts of free radicals such as Reactive Oxygen Species (ROS) which mediate tissue damage resulting in alterations in the cellular macromolecules such as membrane lipids, DNA, and proteins (Kehrer et al, 1990;Islam et al, 2012). There was a significant inhibition in DNA, RNA, and protein content in liver tissue of galactosamine/lipopolysaccharide treated rats (Fyiad et al, 2012).…”
Section: Introductionmentioning
confidence: 99%